A new route of valorization of rice endosperm by-product: Production of polymeric biocomposites. (15th April 2018) - Totaro, Grazia; Sisti, Laura; Vannini, Micaela; Marchese, Paola; Tassoni, Annalisa; Lenucci, Marcello Salvatore; Lamborghini, Matteo; Kalia, Susheel; Celli, Annamaria
Abstract: Rice endosperm, an industrial by-product containing starch as the main component, has been used for the production of novel biocomposites, based on poly(butylene succinate) (PBS). The composites were prepared by melt-mixing, using original or enzymatically-treated rice endosperm. This enzymatic treatment enables the extraction of some high value molecules with antioxidant properties, such as polyphenols. It results that rice endosperm has a good compatibility with the matrix, does not modify the thermal properties of PBS, but notably improves its mechanical performances from a brittle towards a more ductile behaviour. Therefore, rice endosperm by-product, which actually is used for animal feeding, can potentially find a sustainable valorization into new biocomposites with reinforced properties.